Estudio del Desempeño Laboral en el Modelo de Gestión del Talento Humano por Competencias en el Departamento de Gestión de Mercados del GADM Riobamba - Mariño Palacios, Doménica Alexandra (2022)
The purpose of this research is to determine how job performance influences in the human talent management model by competencies in the market management department of GADM Riobamba. This is a descriptive, explanatory, field, and bibliographical research with not experimental design. To carry out the study, definitions, and dimensions of the variables to be addressed, such as Work Performance and Human Talent Management by competencies were considered, in addition, a survey was applied to the officials of the Riobamba GADM market management department, with a questionnaire formulated with the Likert scale. The data collected were used to test the general hypothesis. This was done by applying chi-square. Concluding that job performance and competency-based human talent management is positive however, the situational diagnosis determined that the personnel recruitment and selection process is deficient, Therefore, at the culmination of the study, a proposal is proposed to help improve the market management department at the Riobamba GADM.